Effect of casting temperature on strength and density of plain and blended cement concretes prepared and cured under hot weather conditions. (1st June 2016) - Nasir, Muhammad; Al-Amoudi, Omar S. Baghabra; Al-Gahtani, Husain J.; Maslehuddin, Mohammed
Highlights: The effect of casting temperature on strength and denseness of plain and blended cement concretes has been studied. The optimum casting temperature for OPC and SF cement concrete is 32 °C. The optimum casting temperature for fly ash, very fine fly ash, natural pozzolan and blast furnace slag is 38 °C. Equations relating casting temperature, period of curing and strength and pulse velocity have been developed. Abstract: This paper reports the results of a study conducted to investigate the effect of casting temperature and curing under hot weather conditions on the compressive and tensile strength and density (evaluated by measuring pulse velocity) of plain and blended cement concretes. The concrete specimens were cast at 25, 32, 38 or 45 °C and cured outdoors by covering them with wet burlap. The optimum casting temperature for the plain and blended cement concretes was evaluated by measuring compressive and split tensile strength and pulse velocity. Further, correlations between these properties was developed. The optimum casting temperature was noted to be 32 °C for OPC and SF cement concretes while it was 38 °C for VFFA, FA, GGBFS and NP cement concretes. A good correlation was noted between the concrete casting temperature, period of curing and the concrete properties.